2017
DOI: 10.1002/cne.24291
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channel subtypes are differentially localized to pre‐ and post‐synaptic sites in rat hippocampus

Abstract: Voltage-gated Na+ channels (Nav) modulate neuronal excitability, but the roles of the various Nav subtypes in specific neuronal functions such as synaptic transmission are unclear. We investigated expression of the three major brain Nav subtypes (Nav 1.1, Nav 1.2, Nav 1.6) in area CA1 and dentate gyrus of rat hippocampus. Using light and electron microscopy, we found labeling for all three Nav subtypes on dendrites, dendritic spines, and axon terminals, but the proportion of pre- and post-synaptic labeling for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 83 publications
(132 reference statements)
1
20
0
Order By: Relevance
“…Subsequent investigation in hippocampal pyramidal cells found that Na V 1.2 co-localized with the presynaptic terminal marker VGlut1 using diffraction-limited immunofluorescence techniques, and further showed that Na V 1.6 is expressed throughout dendrites using freeze-fracture immuno-electron microscopy (Lorincz and Nusser, 2010). By contrast, more recent immuno-electron microscopy identified Na V 1.2 throughout dendrites, with an enrichment near postsynaptic densities in spines (Johnson et al, 2017). Whether such apposition with presynaptic terminals accounts for VGlut1 co-localization is unclear.…”
Section: Discussionmentioning
confidence: 90%
“…Subsequent investigation in hippocampal pyramidal cells found that Na V 1.2 co-localized with the presynaptic terminal marker VGlut1 using diffraction-limited immunofluorescence techniques, and further showed that Na V 1.6 is expressed throughout dendrites using freeze-fracture immuno-electron microscopy (Lorincz and Nusser, 2010). By contrast, more recent immuno-electron microscopy identified Na V 1.2 throughout dendrites, with an enrichment near postsynaptic densities in spines (Johnson et al, 2017). Whether such apposition with presynaptic terminals accounts for VGlut1 co-localization is unclear.…”
Section: Discussionmentioning
confidence: 90%
“…These differences in inactivation gating lead to greater isoflurane-induced fast inactivation and inhibition of peak I Na for Na v 1.2 and Na v 1.6 compared with Na v 1.1 at a physiologic holding potential. The greater anesthetic sensitivity of Na v 1.2 and Na v 1.6 provides a plausible mechanism for brain region-and neurotransmitterselective effects of isoflurane on synaptic transmission due to differential expression of Na v subtypes between neuron subtypes and within neuronal compartments (Wood and Baker, 2001;Johnson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal excitability and synaptic transmission show physiologic and pharmacological differences between brain regions and between neurons of different neurotransmitter phenotype (Pinheiro and Mulle, 2008;Spruston, 2008). Some of this heterogeneity could derive from differences in relative expression of various neuronal Na v subtypes having distinct voltage-dependent gating properties, with physiologic and pharmacological implications (Lai and Jan, 2006;Ogiwara et al, 2007;Lorincz and Nusser, 2008b;Johnson et al, 2017). Specific Na v subtypes are selectively expressed on presynaptic and postsynaptic glutamatergic synapses in the hippocampus, consistent with subtype-specific roles in neurotransmitter release and synaptic plasticity (Johnson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations